DELVING SCHOOL LITERACY MOVEMENT: STAGE AND PERCEPTION - I Komang Budiarta (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2022)
School Literacy Movement (SLM) has now become a national movement that is mainly intended to enrich and develop students’ literacy skills. Every school is obligated to carry out this program; moreover, SLM program was initially applied in three public schools in Lembongan village precisely in the academic year 2016/2017. The present qualitative research with a case study design was mainly focused to fathom out the stage and the teachers’ perceptions of the implementation of the program. After administering the research instrument, observation, structured questionnaire, and semi-structured interview, the collected data were analytically triangulated. Finally, the present case study figured out that the implementation of SLM in three public elementary schools at Lembongan village was in the development stage. In addition, teachers considered that teachers’ roles, literacy practices, students’ characters, and literacy rewards were important in the implementation of the SLM program to achieve successful results.